2011
DOI: 10.4269/ajtmh.2011.10-0724
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Caused by Plasmodium vivax Complicated by Acalculous Cholecystitis

Abstract: * RUQ = right upper quadrant; WBC = white blood cell; AAC = acalculous cholecystitis; AST = aspartate aminotransferase; ALT = alanine aminotransferase; HIDA = hepatobiliary iminodiacetic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…A recent review of 16 of these cases compared the presentation and clinical course of the illness across the cases [2]. Our case seems to correspond well with the clinical presentation of AAC in P. falciparum and P. vivax infections, namely nausea, vomiting and abdominal pain in association with mildly deranged liver function tests.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A recent review of 16 of these cases compared the presentation and clinical course of the illness across the cases [2]. Our case seems to correspond well with the clinical presentation of AAC in P. falciparum and P. vivax infections, namely nausea, vomiting and abdominal pain in association with mildly deranged liver function tests.…”
Section: Discussionsupporting
confidence: 76%
“…The majority of the cases were diagnosed using ultrasound, although two also used hepatobiliary iminodiacetic acid (HIDA) scans [2]. Ultrasound is generally accepted as the best first line investigation of AAC due to availability and portability [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, the most common cause of acute abdominal pain is non-specifi c (24 % -44 % ) followed by acute appendicitis (15.9 % -28.1 % ) and then acute biliary disease (2.9 % -9.7 % ) (48) . It is more common in female students than male ones.…”
Section: Cholecystitis/cholelithiasis Epidemiologymentioning
confidence: 99%
“…Previous studies have indicated changes in brain structures in victims of PTSD that were not exposed to chemical agents. 43,44 However, Yamasue and colleagues did perform a separate analysis of covariance looking for the effects of psychological 20 stress on gray matter density. They did not find a significant correlation between regional brain volume reduction and psychological symptoms.…”
Section: Neurological and Cognitive Impairmentsmentioning
confidence: 99%